Analisis Pengaruh Manajemen Laba Kinerja Perusahaan Kualitas Audit Dan Investment Opportunity Set Terhadap Biaya Ekuitas - AMALINA, NUR, Dra. Rina Trisnawati, M.Si, Ak, Ph.d, Drs. Wiyadi, M.M., Ph.D (2017)
The aim of this study is to analyze the effect of earnings management, corporate performance, audit quality, and investment opportunity set on cost of equity. These samples included 461 for JII and LQ-45 during the period 2004-2015. The sampling technique is purposive sampling. Variable earnings management, corporate performance, quality audit, and investment opportunity set as independent variables. Earnings management is proxied by the model Short Term Discretionary Accruals (STDA), proxy corporate performance by Return on Assets (ROA), proxy for audit quality Ukuran Kantor Akuntan Publik (KAP), and the investment opportunity set proxy for Price Earning Ratio (PER). While the dependent variable cost of equity proxy for the model Ohlson. This analysis using multiple linear regression which is previously performed through classical assumption test. The results of research both at the JII and LQ-45 shows that earnings management did not significantly affect the cost of equity, the company's performance did not significantly affect the cost of equity, and Investment opportunity set (IOS) significantly affects the cost of equity. While audit quality affect the cost of equity in companies incorporated in the index JII, but the LQ-45 quality of audit does not affect the cost of equity.